Campus Shuttle Bus Application - Nor, Yusrina; Khairunnisha Zainal, Nur; Farahana Kamsin, Intan (International Journal of Psychosocial Rehabilitation, 2019)
Transportation plays an important role in supporting the implementation of various activities including in universities. Nowadays, many of universities and colleges are also taking initiatives in building a sustainable transportation system by providing campus shuttle service for students. Maintaining a high standard of quality in service and performance are extremely importance to encourage student to make shuttle bus services as their preferred choice. Therefore, this study is aim to improve students’ perceptions towards reliability and effectiveness of campus shuttle system.